El Tribunal Europeo de Derechos Humanos a la luz del Protocolo 14 (2013)
This article is focused on the reforms introduced by Protocol 14 to the European Court of Human Rights (ECHR) that came into force in 2010. It is aimed to make a critical review of the Protocol and to analyze its successes and shortcomings as well as the new configuration that was given to the ECHR. Likewise we will go through the latest reforms that have been introduced by declarations developed in the context of each Ministerial Conference (Interlaken, Izmir and Brighton). Some of the problems of the ECHR will be made clear, particularly in terms of congestion and operation. In the last analysis we will examine the need and appropriateness of the latest reforms to ECHR and conclude if they were enough or if soon new reforms will be required.